Aldose reductase inhibition enhances lens regeneration in mice - Zukin, Leonid M. (Chem Biol Interact, 2019)
After cataract surgery, epithelial cells lining the anterior lens capsule can transition to one of two divergent pathways, including fibrosis which leads to posterior capsular opacification (PCO), or lens fiber cell differentiation which leads to regeneration of lens material. We previously showed that the PCO response can be suppressed with aldose reductase (AR) inhibitors. In this present study we show that AR inhibition, both genetic and pharmacologic with Sorbinil, can augment the process of lens regeneration. Extracapsular lens extraction (ECLE) was carried out in C57BL/6 (WT), AR overexpression (AR-Tg), and AR knockout (ARKO) mice, and in some cases in mice treated with the AR inhibitor sorbinil. Whole eyes were harvested approximately 8 weeks after ECLE and evaluated by histological analysis and immunostaining for the fiber cell marker γ-crystallin. All eyes examined for lens regeneration were paraffin embedded for serial sectioning to produce three-dimensional reconstructed models of lens morphology and size. We observed that AR-null mice respond to ECLE by regenerating a lens-like structure with a circular shape and array of cell nuclei reminiscent of the lens bow region typical of the native mammalian lens. Although WT and AR-Tg eyes also produced some regenerated lens material after ECLE, their structures were consistently smaller than ARKO regenerated lenses. WT mice treated with sorbinil showed higher levels of lens regeneration after ECLE compared to WT mice, as assessed by size and three-dimensional morphology. Altogether, this study adds evidence for a critical role for AR in the response of lens epithelial cells to cataract extraction and lens regeneration.